Validation of a New Software eAT24 Used to Assess Dietary Intake in the Adult Portuguese Population - Goios, AC (2020)
Objective: The aim of the current study was to evaluate the accuracy of the new software eAT24 used to assess dietary intake in the National Food, Nutrition and Physical Activity Survey (IAN-AF) against urinary biomarkers: N (nitrogen), K (potassium) and Na (sodium). Design: We conducted a cross-sectional study. Two non-consecutive 24-h dietary recalls (24-HDR) were applied, and a 24-h urine sample was collected. We examined differences between estimates from dietary and urine measures, Pearson correlation coefficients were calculated and the Bland-Altman plots were drawn. Multiple linear regression was used to evaluate the factors associated with the difference between estimates. Setting: Sub-sample from the Portuguese IAN-AF sampling frame. Participants: Ninety-five adults (men and women) aged 18-84 years. Results: The estimated intake calculated using the dietary recall data was lower than that estimated from urinary excretion for the three biomarkers studied (protein 94·3 v. 100·4 g/d, K 3212 v. 3416 mg/d and Na 3489 v. 4003 mg/d). Considering 2 d of recall, the deattenuated correlation coefficients were 0·33, 0·64 and 0·26 for protein, K and Na, respectively. For protein, differences between dietary and urinary estimates varied according to BMI (β = -1·96, P = 0·017). The energy intake and 24-h urine volume were significantly associated with the difference between estimates for protein (β = 0·03, P < 0·001 and β = -0·02, P = 0·002, respectively), K (β = 0·71, P < 0·001 and β = -0·42, P = 0·040, respectively) and Na (β = 1·55, P < 0·001 and β = -0·81, P = 0·011, respectively). Conclusions: The new software eAT24 performed well in estimating protein and K intakes, but lesser so in estimating Na intake, using two non-consecutive 24-HDR.